Intellectual Property and Artificial Intelligence - Challenges and Prospects: An Analytical Study - Omar Mahjoub Mohammed Al-Hussain, (International Journal of Law Research and Studies, 2025)
This research explores the fundamental challenges posed by Artificial Intelligence (AI) to traditional intellectual property (IP) systems, which were originally designed to protect human creativity. By analyzing the theoretical framework, previous studies, and international case studies, the research highlights key issues such as legislative gaps, the difficulty in identifying the "author" or "inventor" of AI-generated outputs, and the complexity in establishing ownership and originality.The findings reveal an emerging global judicial consensus refusing to recognize AI itself as a rights holder, emphasizing that humans must remain central to these systems. Conversely, regulatory approaches vary significantly worldwide, from European rigor to Asian flexibility, necessitating the development of adaptable and balanced frameworks.The study proposes a future vision based on integrating innovators' rights with the public interest, through graduated protection systems, enhanced international cooperation, and the leveraging of emerging technologies like blockchain. It concludes with a set of legislative, technical, and practical recommendations to strengthen protection and foster innovation in this digital age.
Keywords: Artificial Intelligence; Intellectual Property Rights; Innovation; Invention; Generative Artificial Intelligence